Práticas pedagógicas nos laboratórios de educação digital: um olhar acerca do currículo de tecnologias e das aprendizagens - Tadeu, Tânia (Universidade Federal de São Carlos, 2023)
The theme of this research refers to the technologies used in education as pedagogical tools integrated to the Curriculum of the City of São Paulo and to the principles that involve digital culture, protagonist, autonomy, inventiveness, collaboration, reflective thinking and information as a construction of knowledge. The aim of the research is to analyze, from the perceptions of the Teachers of Digital Education (POED), how the pedagogical practices take place in the Digital Education Laboratories (LED), present in all elementary schools in the city of São Paulo, through the implementation of the Technologies for Learning Curriculum (TPA), from 2017 to 2022. The theoretical foundations of the research are based on Paulo Freire, since it was during his administration as Municipal Secretary (1989 - 1991) that the Genesis Project was established, with the computer in the teaching-learning process and including the assumptions of the conceptions of programming language and research on the use of computers in pedagogical and curricular practices. Narrative interviews were used as a constituent methodological resource as an instrument of investigation, enabling dialogue with what happens with the educators who work in the digital education labs, in a qualitative approach, based on the referential provided by Jovchelovitch and Bauer (2002). The bibliographic review of the constitution of educational computing in the city of São Paulo, the systematic mapping of literature carried out in the academic databases Brazilian Digital Library of Theses and Dissertations (BDTD) and Catalogs of Theses and Dissertations, Graduate level personnel improvement coordination (CAPES),and the documents and references to existing technologies throughout the history of the municipal education system of São Paulo, were paths followed for a better understanding of the current curriculum document. The final considerations pointed out that, through the perceptions arising from the narrative interviews, the pedagogical practices developed after the implementation of the technology curriculum were re-signified by continuous training and respect for the territories in which the schools are located. Teachers emphasized the importance of partnerships among teachers and felt stronger as learning mediators. The consideration of history, identity, and previous experiences were pointed out as significant for the success of the practices carried out, even though there are still many challenges to be overcome, caused especially by the pandemic period.
Pedagogical practices in digital education laboratories: a look at the technology and learning curriculum
Keywords: Currículo de Tecnologias; Tecnologia Educacional; Práticas Pedagógicas; Technology Curriculum; Educational Technology; Pedagogical Practices; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO